The Proposal of a Fuzzy Ahp Based Model for the Efficiency Analysis of Technopark - Serap Tepe; A.halim Zaim (Cumhuriyet Üniversitesi İktisadi ve İdari Bilimler Dergisi)
In thepaper, it is proposed a model to evaluate the efficiency of technopark byperforming an activity analysis on the productivity of the technoparkstructure, aiming to contribute to the innovative movement and sustainabledevelopment goals, which may result in huge amounts of increase in added-valueof Turkey’s technological development. The initial point of the paper is todefine technopark structure and activities, to determine and eliminateuncertainties concerning structure and operation. Technoparks are investigatedbased upon their management, firms & incubation firms, R&D activities,and cooperation level among university-industry. In the paper, a fuzzy analytichierarchy process method is used. The paper includes four technoparks thatoperate in Istanbul. By applying the developed model, the results of theperformance evaluation are reached and the results are interpreted. It isthought that the findings obtained from this research will be beneficial forall stakeholders related to technoparks.